Parametric description of 3-dimensional surface of craniofacial shape - Suwardhi, Deni; Setan, Halim; Majid, Zulkepli; Ahmad, Anuar; Chong, Albert K. (2004)
This paper describes two methods to create a parametric model of a craniofacial structure. The first method uses spherical harmonics (SH) which describe the surface determined by mapping to a sphere. The second method is Hierarchical B-Spline which split the surface into several numbers of patches to obtain a given shape. The usual way of storing craniofacial data is voxel images that allow visual capturing of the objects, but it is lack of structural description since they are based on huge list of numbers. On the other hand new medical imaging modalities, such as Digital Close-Range Photogrammetry and Laser-scanner produce precise and smooth models of human tissues. Until now the model used in such applications are rough polygon meshes.